How Employee Engagement Will Lead to Performance: A Case of IBISMA- A Non-Profit Organization - Kenneh, Mohammed; Palupi, Majang; Suratman, Andriyastuti (CV. Lenggogeni Data Publishing, 2024)
Employee engagement and its impact on organizational performance have received significant attention over the past two decades. This research delves into the factors that influence the impact of employee engagement on IBISMA's performance as a non-profit organization. It explores the various organizational factors that influence and shape employee engagement. The researchers adopted a qualitative research methodology. An inductive approach was employed to conduct interviews, allowing for a deeper understanding of the factors that affect employee engagement. The resulting data was then subjected to thematic analysis for further examination. The main findings of the study reveal a clear understanding of the factors that influence the impact of employee engagement that lead to performance of IBISMA. It has been identified in this research that diminished levels of engagement significantly impact employee commitment and motivation. Several factors contribute to the observed decline in employee engagement, including job design, ineffective communication practices, workplace culture, insufficient recognition-based rewards, and career growth and development. Based on the findings above, suggested recommendations are made in order to increase engagement at IBISMA through weekly strategic discussions, establish a robust and consistent communication system, establish a reward and recognition system to motivate and encourage work engagement, and establish a performance evaluation system for better engagement. Keywords: employee engagement, organization performance, effective leadership, IBISMA